New Zealand Occupational Hygiene Society (NZOHS) Conference: Guest Editorial and Book of Abstracts - Cheung, Kerry (New Zealand Journal of Health and Safety Practice, 2025)
The New Zealand Occupational Hygiene Society (NZOHS) Work Related Health Conference 2025 was held from 26–28 May at the Hilton Auckland, marking the fourth instalment of our biannual event. With the theme "Challenges, Changes, Solutions", the conference brought together over 160 delegates from across New Zealand and 13 other countries, including Australia, Canada, Indonesia, South Korea, the Netherlands, South Africa, and the United States. It was preceded by having the privilege of hosting the International Occupational Hygiene Association (IOHA) Board Meeting. This year’s event truly lived up to its title as a work-related health conference, showcasing the breadth of presentations from various health & safety disciplines and from different countries around the world. The programme featured four keynote speakers, four continuing education sessions, 27 concurrent presentations, and four practical workshops. The diversity of topics reflected the complexity of modern work-related health issues – ranging from best practice, occupational hygiene and health to psychosocial risk, human factors and ergonomics, and technology.